2017
DOI: 10.1080/15504263.2017.1326651
|View full text |Cite
|
Sign up to set email alerts
|

An Online Survey of Family Members' Beliefs and Attitudes About Smoking and Mental Illness

Abstract: Objective Family beliefs about smoking and cessation may influence whether individuals with mental illness who smoke use effective cessation treatment. We surveyed family members online regarding beliefs about smoking and cessation among people with mental illness. Method Two hundred fifty-six family members of individuals with mental illness completed an online survey. Responses were summarized and t tests were used to compare responses based on the family member’s smoking status. Results One-quarter of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…person intervention for smokers with mental illness to include in person recruitment strategies. A recent survey of family members' beliefs and attitudes about smoking and mental illness revealed that many family members of smokers with mental illness are uncertain about the safety of cessation treatment for individuals with mental illness [10]. All of the support persons recruited for the present study from a NAMI state affiliate were family members of individuals with mental illness who smoked.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…person intervention for smokers with mental illness to include in person recruitment strategies. A recent survey of family members' beliefs and attitudes about smoking and mental illness revealed that many family members of smokers with mental illness are uncertain about the safety of cessation treatment for individuals with mental illness [10]. All of the support persons recruited for the present study from a NAMI state affiliate were family members of individuals with mental illness who smoked.…”
Section: Discussionmentioning
confidence: 99%
“…Content was added to the original support person intervention manual to address common beliefs and concerns about smoking and mental illness (e.g., tobacco is necessary self-medication, smoking cessation medication is harmful). The decision to modify the support person intervention content was informed by the literature documenting prevailing myths and concerns that have likely contributed to tobacco use among people with mental illness [10,11,15], and based on informal conversations with NAMI leaders and family members of persons with mental illness regarding their beliefs and concerns about smoking and cessation treatment. The original evidence-based coaching techniques used in the support person intervention were not substantially modified during this process.…”
Section: Support Person Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…People with mental health conditions misperceive smoking as an activity that helps with mental health symptom management. ( Aschbrenner et al, 2017b , Lawn et al, 2015 ) This belief is supported by family members or peers of people with mental health conditions, who incorrectly believe that quitting smoking may interfere with mental health functioning. ( Hyland et al, 2017 ) Such misconceptions about smoking and mental health likely create social spaces where smoking is acceptable or even encouraged.…”
Section: Introductionmentioning
confidence: 99%